Farmers' attitudes towards biodiversity shape the effectiveness of biodiversity-friendly management practices for wild bees, but not plants and spiders - Jeroen Scheper; David Kleijn; Fabian Klebl; Anneli Adler; András Báldi; Ignasi Bartomeus; Vincent Bretagnolle; J.P. Reinier De Vries; Sabrina Gaba; Maura Ganz; José M. Herrera; Felix Herzog; et al. (Biological Conservation, 2026)

Safe and sustainable-by-design valorization of hop bioactives: Integrating techno-economic performance, environmental assessment, circularity and safety in the bioeconomy era - Aroa Carballido; Ana Arias; Anna Stasiłowicz-Krzemień; Gumersindo Feijoo; Gerardo Álvarez-Rivera; Maria Teresa Moreira (Innovative Food Science & Emerging Technologies, 2026)

Maternal mycoestrogen exposure in relation to timing of birth and placental corticotropin releasing hormone concentrations in a U.S. pregnancy cohort - Alyssa Juenke; Megan C. Hansel; Carolyn W. Kinkade; Anita Brinker; Maria Bowman; Roger Smith; Richard K. Miller; Jessica Brunner; Brian Buckley; Thomas G. O’Connor; Lauren M. Aleksunes; Zorimar Rivera- Núñez; et al. (Reproductive Toxicology, 2026)

Beyond Coverage: A Systematic Review and Thematic Analysis of Delivery, Compliance, Equity and Impact in Mass Deworming for Soil-Transmitted Helminths - Harley M. Rodriguez; Angelica Marie B. Rostata; Jan Joseph Rainer Christorey Maria Salgado; Timothy Liam D. Rivera; Jose Ma. M. Angeles (Acta Parasitologica, 2026)

Rare Amazonian canids revealed: record camera trap detections of the short-eared dog (Atelocynus microtis) and bush dog (Speothos venaticus) in southeastern Peru - Sam Pottie; Erin Marcela Rivera Groves; Flor Maria Perez Mullisaca; Caleb Jonatan Quispe Quispe; Rosio Vega Quispe; Christopher Beirne; Andrew Whitworth; Adrian Forsyth (Mammal Research, 2026)

Trends and risk factors of antimicrobial resistance of Neisseria gonorrhoeae in Catalonia, Spain, 2022–2023 - Mercè Herrero; Sonia Broner; Naiana Pastrana-Batalla; Eduard Anfruns; Evelin López-Corbeto; Victoria González; Judit Serra-Pladevall; Nieves Larrosa; Jacobo Mendioroz; Pilar Ciruela; Yuliya Poliakova; Mateu Espasa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Biological Response Matrix for risk management of bottom-cultured Peruvian scallops under oxygen deficiency, temperature, and exposure-time stressors - Rebeca Campos-Cuellar; Rosa Cueto-Vega; Maria Rivera-Chira; Jorge Cardich; Jorge Tam; Jonathan Flye-Saint-Marie; Arturo Aguirre-Velarde (Aquaculture, 2026)

Environmental life cycle assessment of novel PV systems for desert conditions - Jose Maria Cruz; Ximena Schmidt Rivera; Francisca Jalil-Vega; Raúl O'Ryan; Felipe Valencia; Jorge Rabanal-Arabach; Eduardo Ayllón Opazo; Paulina Andrea Morris Carmona; Patricio Larrain Yañez (Sustainable Production and Consumption, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Combined Biofortification of Durum Wheat with Zinc and Selenium: Effects on Semolina and Pasta Nutrient Accumulation and Yield - Carlos García-Latorre; Angélica Rivera-Martín; María Dolores Reynolds-Marzal; Maria J. Poblaciones (Biological Trace Element Research, 2026)

Identification of common types of plastics by vibrational spectroscopic techniques - Maria P.Garcia Tovar; Maria A.Villarreal Blanco; Oliva M. Primera-Pedrozo; Macy K. Christianson; Chih-Feng Wang; Pavel Valencia Acuña; John H. Miller; Luis de la Torre; Samuel P.Hernández Rivera (Resources, Conservation and Recycling, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

From ashes to old-growth forests: How do long-term changes in forest structure affect understory plant diversity after wildfires in Yellowstone National Park? - Zhengxue Zhu; Robert W. Pal; Stefano Chelli; Marco Cervellini; Roberto Canullo; Luciano Ludovico Maria De Benedictis; Alysia Cox; Ariana Rivera Añazco; Sandor Bartha; Giandiego Campetella (Forest Ecology and Management, 2026)

Patentability of natural products from Venomous Organisms: A guide for life science researchers - Maria P. Ikonomopoulou; Gregor Anderluh; Sahin Coskun; Fernando Merello Luna; Maria Vittoria Modica; Jan Procházka; Esperanza Rivera-de-Torre; Andrea Tarallo; Aude Violette (Toxicon, 2026)

The biomedical engineer’s pledge: overview and context - Antoni Ivorra; Txetxu Ausín; Laura Becerra-Fajardo; Antonio J. del Ama; Jesús Minguillón; Aracelys García-Moreno; Jordi Aguiló; Filipe Oliveira Barroso; Bart Bijnens; Oscar Camara; Sara Capdevila; Roger Castellanos Fernandez; et al. (Medical & Biological Engineering & Computing, 2026)
Although biomedical engineering (BME) is a profession with ethical responsibilities comparable to those in medicine, it has, until now, lacked a counterpart to the Hippocratic Oath. While professional societies have established codes of ethics for biomedical engineers, these documents lack the symbolic and ceremonial significance of an oath or pledge. By contrast, the recitation of the Hippocratic Oath, or its modern version, the “Physician’s Pledge,” serves as a powerful rite of passage for medical students, fostering a strong sense of ethical duty at the start of their professional journey. However, the content of the Hippocratic Oath includes elements specific to clinical practice and is not directly applicable to biomedical engineering. To fill this gap, we have created a “Biomedical Engineer’s Pledge,” comprising a preamble, ten promises, and a concluding statement, to inspire ethical awareness and establish a meaningful graduation tradition. Graphical abstract

Multi-scale observations during the 2024 mass coral bleaching event on Heron Reef, Australia - Devin A. Rowell; Nicholas M. Hammerman; Kirsten M. Golding; Tania Marie Kenyon; Zoe Meziere; Courtney Morgans; Kristen Taylor Brown; Faye F. Diederiks; David E. Carrasco Rivera; Karen Eigeland; Roima Paewai-Huggins; Kathryn Markey; et al. (Marine Biology, 2026)

Erratum to “Extremely low-frequency magnetic fields (ELF-MF) and radiofrequency: Risk of childhood CNS tumors in a city with elevated ELF-MF exposure” [Environ. Res. Volume 286, Part 2, 1 December 2025, 122858] - Víctor Correa‐Correa; Juan Carlos Núñez‐Enríquez; Gabor Mezei; Roberto Rivera‐Luna; José Gabriel Peñaloza‐González; Salvador Daniel Rivas-Carrillo; Cuauhtémoc Gil Ortiz-Mejía; Claudia Flores-Robles; Erick Velasco-Ramírez; Mario Alexis del Real-Gallegos; Janet Flores‐Lujano; Fernanda Valeria Flores-Pérez; et al. (Environmental Research, 2025)

Extremely low-frequency magnetic fields (ELF-MF) and radiofrequency: Risk of childhood CNS tumors in a city with elevated ELF-MF exposure - Víctor Correa‐Correa; Juan Carlos Núñez‐Enríquez; Gabor Mezei; Roberto Rivera‐Luna; José Gabriel Peñaloza‐González; Salvador Daniel Rivas-Carrillo; Cuauhtémoc Gil Ortiz-Mejía; Claudia Flores-Robles; Erick Velasco-Ramírez; Mario Alexis del Real-Gallegos; Janet Flores‐Lujano; Fernanda Valeria Flores-Pérez; et al. (Environmental Research, 2025)

Stream Degradation: Direct and Indirect Impacts of Amazonian Deforestation - Gabriel Martins Cruz; Ana Paula Justino Faria; Josinete Sampaio Monteles; Karina Dias-Silva; Lilian Casatti; Juan Mateo Rivera-Perez; Rafael Costa Bastos; Victor Rennan Santos Ferreira; Leandro Schlemmer Brasil; Thaisa Sala Michelan; Lenize Batista Calvão; Everton Cruz da Silva; et al. (Ecosystems, 2025)

Risk in the quality of aquatic ecosystems exposed to pesticides in a natural protected area of influence in western Mexico - Cruz-Esquivel Ángel; Martínez-Rivera Luis Manuel; Sandoval-Pinto Maria Elena; Meza-Rodríguez Demetrio; Peregrina-Lucano Alejandro Aaron (Environmental Monitoring and Assessment, 2025)

Modulation of immune response and tissue repair mechanisms in the gill filaments of Atlantic salmon (Salmo salar) affected by complex gill disease (CGD) in a marine open sea-cage environment - Mabel Vidal; Maria Jesús Santillán-Araneda; Alexis Rivera; Merari Goldstein; Sebastián Reyes-Cerpa; Marcos Mancilla; Patricio Bustos; Eva Vallejos-Vidal; Felipe E. Reyes-López (Fish & Shellfish Immunology, 2025)

Structural insights into ABA receptor agonists reveal critical features to optimize and design a broad-spectrum ABA signaling activator - Mar Bono; Cristian Mayordomo; Alberto Coego; Jonatan Illescas-Miranda; Maria Rivera-Moreno; Lourdes Infantes; Pablo López-Carracedo; Mayra Sanchez-Olvera; Constanza Martin-Vasquez; Gaston A. Pizzio; Javier Merino; Javier Forment; et al. (Molecular Plant, 2025)

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

Exploring cadmium bioaccumulation and bioremediation mechanisms and related genes in soil microorganisms: a review - Nataly J. Galan-Freyle; Yani Aranguren-Diaz; Susana L. Ospina-Maldonado; Paula F. Chapuel-Aguillon; Maria F. Pertuz-Peña; Samuel P. Hernandez-Rivera; Leonardo C. Pacheco-Londoño (Environmental Science and Pollution Research, 2025)
Cadmium (Cd) is a highly toxic heavy metal that poses serious environmental and health risks. It reduces soil fertility and can cause renal failure, liver damage, bone fractures, hypercalciuria, and cancer in humans. Cd contamination in soil, originating from both natural and human activities, is especially concerning because it bioaccumulates in plants, entering the food chain and affecting crops like tomatoes, rice, cocoa, and lettuce. Understanding the mechanisms of Cd bioaccumulation and bioremediation in microorganisms isolated from Cd-contaminated soils is crucial for developing effective strategies to mitigate Cd contamination in soils. This review highlights recent studies on the mechanisms of Cd uptake and detoxification in microbes, emphasizing genes and enzymes that mediate Cd response. Microbial species such as Pseudomonas aeruginosa , Burkholderia sp. , and Bacillus subtilis , along with various fungal species, show resistance mechanisms influenced by genes that enhance their Cd tolerance. Enzymes like peroxidases, ATPase, and sucrose play roles in Cd stress responses. Key genes such as czcA , czcD , zntA , cadA , and cadD encode proteins that improve their tolerance to Cd. These microbial mechanisms offer sustainable solutions to improve soil health, crop productivity, and environmental safety. Future research should focus on engineering microorganisms with improved Cd-binding mechanisms, optimizing their effectiveness across different soil types, pH levels, and exposure durations.

Dental and temporomandibular joint pathology of the North American wolverine (Gulo gulo luscus) - Maria Soltero-Rivera; Janny V. Evenhuis; Boaz Arzi; Frank J.M. Verstraete (Journal of Comparative Pathology, 2025)

Phosphorylation/dephosphorylation-mediated regulation of ABI1/2 activity and stability for fine-tuning ABA signaling - Mar Bono; Maria Rivera-Moreno; Armando Albert; Pedro L. Rodriguez (Molecular Plant, 2025)

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

Exposure to toxic metal(loid)s via breastmilk and stunting in infants living in the Lake Atitlán watershed, Guatemala - Sandra Rodríguez Quintana; Frank A. von Hippel; Mónica Orozco; Noel Solomons; Dean Billheimer; Maria A. Sans-Fuentes; Mary Kay Amistadi; Sam Sneed; Paloma Beamer; Alejandra Zamora; Eileen Rivera; Ruth Forsten; et al. (Environmental Pollution, 2025)

Ecotoxicity of graphene oxides on human and murine cell lines, bacteria, and microalgae: Insights and perspectives for environmental applications - Ana Maria Gagneten; Wilfredo Rondan; Josefina Schmuck; Ulises Reno; Luciana Regaldo; Manuel Houre; Boris Rodenak Kladniew; Maria Rivera; Jaime Vazquez; José Javier Sáez Acuña; Ana Champi (Journal of Applied Phycology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Land use change for shrimp aquaculture ponds and its impact on water use in Marismas Nacionales, Mexico - Carlos Ivan Salinas Espinosa; Jushiro Cepeda Morales; Oscar Ubisha Hernandez Almeida; Juan Pablo Rivera Caicedo; Bernardino Ricardo Eaton Gonzalez; Carlos Francisco Ortiz Paniagua; Maria Alejandra Quintero Morales (Wetlands Ecology and Management, 2025)

Dental and temporomandibular joint pathology of the North American river otter (Lontra canadensis) - Janny V. Evenhuis; Maria Soltero-Rivera; Boaz Arzi; Frank J.M. Verstraete (Journal of Comparative Pathology, 2025)

Epidemiological Study on Humans, Animals and Snails for Schistosomiasis in Two Endemic Municipalities Nearing Elimination in Bohol, the Philippines - Jose Ma. M. Angeles; Katrina Theresa M. Balboa; Frances Paula L. Miaral; Klyde Irene M. Ligot; Kevin Austin L. Ona; Maria Luz B. Belleza; Elena A. Villacorte; Pilarita T. Rivera; Shin-ichiro Kawazu; Aya Yajima (Acta Parasitologica, 2025)

Is climate change the problem? A feminist analysis of climate change discourses in Spain and Catalonia - Maria Borràs-Escayola; Federica Ravera; Marta G. Rivera Ferre (Environmental Science & Policy, 2025)

Long-term impact of Hurricane Maria on point-of-use drinking water quality in Puerto Rico and associated potential adverse health effects - Yishan Lin; Guangyu Li; Maria Sevillano Rivera; Tao Jiang; Irmarie Cotto; Corey M.G. Carpenter; Stephanie L. Rich; Roger W. Giese; Damian E. Helbling; Ingrid Y. Padilla; Zaira Rosario-Pabón; Akram N. Alshawabkeh; et al. (Water Research, 2024)

Factors influencing fumonisin B1 contamination in maize: insights from two production regions in Costa Rica - Katherine Sánchez-Zúñiga; William Rivera-Méndez; Stefany Campos-Boza; Emanuel Araya-Valverde; Frank Solano-Campos; Maria Vinas (Mycotoxin Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Comprehensive analysis of the phytochemical composition and antitumoral activity of an olive pomace extract obtained by mechanical pressing - Diana Melo Ferreira; Juliana Barreto-Peixoto; Nelson Andrade; Susana Machado; Cláudia Silva; Joana C. Lobo; Maria A. Nunes; Gerardo Álvarez-Rivera; Elena Ibáñez; Alejandro Cifuentes; Fátima Martel; M. Beatriz P.P. Oliveira; et al. (Food Bioscience, 2024)

Groundtruthing nitrogen isotopes as a symbiosis proxy using the facultatively symbiotic coral Oculina arbuscula - Heather A. Donnelly; Maria Valadez-Ingersoll; Marcus Lin; Hanny E. Rivera; Carlos A. Tramonte; Sarah W. Davies; Xingchen Tony Wang (Frontiers in Marine Science, 2024)
The resilience of coral reefs in oligotrophic, (sub)tropical oceans is largely due to the symbiotic relationship between scleractinian corals and Symbiodiniaceae algae, which enables efficient internal nutrient recycling. Investigating the history of this coral symbiosis can provide insights into its role in sustaining the health of both present and future coral reefs. The isotopic composition of organic nitrogen ( 15 N/ 14 N or δ 15 N) bound within coral skeletons has been utilized to trace the existence of symbiosis in fossil corals, suggesting that coral symbiosis dates back to at least 210 million years ago. The basis of this proxy is that symbiotic corals are expected to exhibit lower δ 15 N compared to their non-symbiotic (aposymbiotic) counterparts within the same environments, owing to internal nitrogen recycling between the coral host and algal symbiont, and reduced leakage of low-δ 15 N ammonium into seawater. However, this hypothesis has not been adequately tested in contemporary settings. In a laboratory experiment, we examined the δ 15 N differences between the symbiotic and aposymbiotic branches within the same genetic backgrounds of the facultatively symbiotic coral Oculina arbuscula under well-fed conditions. Across five different genotypes in two separate experiments, symbiotic branches consistently showed lower δ 15 N than their aposymbiotic counterparts. These findings corroborate the use of δ 15 N as a proxy for identifying coral symbiosis in the past, particularly when multiple species of corals coexisted in the same environments.

Implementing magnetically-active Sn-based nanocomposites in hexavalent chromium removal from drinking water - Theopoula Asimakidou; Kyriaki Kalaitzidou; Fani Pinakidou; Ting Zhou; Pilar Rivera-Gil; Lluis Balcells; Manassis Mitrakas; Antonios Makridis; Maria Katsikini; George Vourlias; Konstantinos Chrissafis; Konstantinos Simeonidis (Chemosphere, 2024)

Associations of prenatal exposure to phthalates and their mixture with lung function in Mexican children - Cheng-Yang Hu; Cecilia S. Alcala; Hector Lamadrid-Figueroa; Marcela Tamayo-Ortiz; Adriana Mercado-Garcia; Nadya Rivera Rivera; Allan C. Just; Chris Gennings; Martha María Téllez-Rojo; Robert O. Wright; Rosalind J. Wright; Kecia N. Carroll; et al. (Journal of Hazardous Materials, 2024)

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Sustaining altitude pastures in mountain landscapes–a fuzzy cognitive model approach - Catarina Esgalhado; Teresa Pinto-Correia; Stefano Targetti; Claude Napoléone; Maria Rivera (Science of The Total Environment, 2024)

Nature’s contribution to people provided by pastoral systems across European, African, and Middle East Mediterranean countries: trends, approaches and gaps - Graeme Dean; Matteo Francioni; Marco Toderi; Feliu López-i-Gelats; Laura Trozzo; Marta G. Rivera-Ferre; Antonello Franca; Giovanni M. Altana; Maria Karatassiou; Zoi M. Parissi; Eleni M. Abraham; Athanasios Ragkos; et al. (Regional Environmental Change, 2024)
Mediterranean pastoral systems are providers of a wide array of Nature’s Contribution to People (NCP). They are ‘complex systems’ characterized by limited resources and socio-economic dynamics currently threatened by climate and social changes. Despite a growing number of scientific articles dealing with NCP, there is a high risk that the existing literature has left out the complexity of such systems. In the light of ongoing social, economic, and climatic changes in the Mediterranean basin, neglecting the complexity of pastoral systems can lead to significant research biases, missing the priorities affecting the stability and continuity of such systems. A combination of frameworks of analysis provided by the Millennium Ecosystem Assessment and by the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services was applied to understand if and to what extent the complexity of Mediterranean pastoral systems has been considered in the available literature. Most of the 126 papers report studies conducted in the European Union zone (102 papers), with the majority in Spain (50). Fewer studies have been conducted in the Middle East (15 papers) and Africa zones (9 papers). Despite results confirming the importance of pastoral systems as providers of NCP, most of the eligible papers focused on regulating NCP. A lack of a multisectoral approach and integration of knowledge suggests that the complexity of Mediterranean pastoral systems has been overlooked by researchers. The creation of ‘hybrid knowledge’ bridging the expertise of different stakeholders could be the key ingredient to properly address the complexity of Mediterranean pastoral systems.

Rhizobium hidalgonense and Rhizobium redzepovicii as faba bean (Vicia faba L.) microsymbionts in Mexican soils - Flor N. Rivera Ortuña; Joseph Guevara-Luna; Jun Yan; Eloisa Lopez Amezcua; Ivan Arroyo-Herrera; Yan Li; Maria Soledad Vásquez-Murrieta; Danae Rojas Arellano; En Tao Wang (Archives of Microbiology, 2024)

Validation of the intrinsic vulnerability to pollution of fractured siliciclastic aquifers using natural background levels - Luisa Casadiegos-Agudelo; Maria Alejandra Cetina-Tarazona; Isabel Cristina Dominguez-Rivera; Sully Gomez-Isidro (Groundwater for Sustainable Development, 2024)

Alternative hydraulic concretes based on calcium sulfate-granulated blast furnace slag composites - Ricardo X. Magallanes-Rivera; Maria Elena Bazaldúa-Medellín; José Iván Escalante-Garcia (Journal of Cleaner Production, 2024)

A case study on pharmaceutical residues and antimicrobial resistance genes in Costa Rican rivers: A possible route of contamination for feline and other species - Seiling Vargas-Villalobos; Félix Hernández; David Fabregat-Safont; Denis Salas-González; Francisco Quesada-Alvarado; Ana Maria Botero-Coy; Fernando Esperón; Bárbara Martín-Maldonado; Juan Monrós-Gonzalez; Clemens Ruepert; Sandra Estrada-König; Josué Rivera-Castillo; et al. (Environmental Research, 2024)

Actions to strengthen the contribution of small farms and small food businesses to food security in Europe - Olga M. Moreno-Pérez; Laura Arnalte-Mur; Pedro Cerrada-Serra; Victor Martinez-Gomez; Anda Adamsone-Fiskovica; Bjørkhaug; Gianluca Brunori; Marta Czekaj; Dominic Duckett; Paola A. Hernández; Christina Noble; Teresa Pinto-Correia; et al. (Food Security, 2024)
This study stems from a participatory foresight exercise conducted in nine Mediterranean, Baltic, Nordic and Eastern European regions, aiming to strengthen the role of small farms and small food businesses in ensuring food security. A wide range of stakeholders participated by attending workshops. They represented farmers’ organisations, food businesses, consumers’ organisations, NGOs, researchers, extension services, professional groups, and administration and public bodies. The actions proposed by participants are scanned and categorised around six broad objectives, stakeholders’ priorities and their underlying beliefs and preconceptions are discussed around the current debates of the literature, and the drivers that influence the feasibility of the proposed actions are discussed. Furthermore, the alignment of stakeholders’ -driven objectives with the European Strategies on food, agriculture, and rural areas is examined, with a focus on: (i) the EU Farm to Fork Strategy, (ii) the Rural Action Plan contained in the Long-Term Vision of Rural Areas developed by the EU Commission, and (iii) the Common Agricultural Policy in force since January 2023.

Removal of hexavalent chromium using zero-valent magnesium in a continuous flow system - Giulia Maria Curcio; Elvis Gribaldo Aucancela Rivera; Carlo Limonti; Tiziana Andreoli; Rajandrea Sethi; Alessio Siciliano (Journal of Water Process Engineering, 2023)

Gravimetric inversion and three-dimensional geological modelling of the Piquiri Syenite Massif, southern Brazil - Victor Soares Cardoso; Maria de Fátima Bitencourt; Jairo Francisco Savian; Robson dos Santos Aquino; Cristiane Butori Rivera (Journal of Geodynamics, 2023)

Analyzing the Decision of Not Purchasing Fruit and Vegetables - Andres Silva; Maria Paz Rivera; Samuel Durán (Journal of Nutrition Education and Behavior, 2023)

Gingiva-derived Stromal Cells Isolated from Cats Affected with Tooth Resorption Exhibit Increased Apoptosis, Inflammation, and Oxidative Stress while Experiencing Deteriorated Expansion and Anti-Oxidative Defense - Maria Soltero-Rivera; Sylwia Groborz; Maciej Janeczek; Justyna Kornicka; Monika Wierzgon; Boaz Arzi; Krzysztof Marycz (Stem Cell Reviews and Reports, 2023)

Epidemiology and antimicrobial resistance profile of Neisseria gonorrhoeae in Catalonia, Spain, 2016–2019 - Mercè Herrero; Sonia Broner; Adrià Cruells; Silvia Esteve; Lourdes Ferré; Jacobo Mendioroz; Mireia Jané; Pilar Ciruela; Miguel Ángel Benítez; Jordi Bosch; Cristina Pitart; Frederic Ballester; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Antimicrobial resistance data for Neisseria gonorrhoeae is globally sparse and resistant strains are emerging in Catalonia. We aim to describe epidemiological and antimicrobial resistance in all patients infected with N. gonorrhoeae during the period from 2016 to 2019, using available antimicrobial susceptibility data. We retrospectively analysed confirmed N. gonorrhoeae cases notified to Catalonia’s microbiological reporting system. Antibiotic susceptibility testing (azithromycin, cefixime, ceftriaxone, ciprofloxacin, penicillin, spectinomycin, and tetracycline) was assessed using clinical breakpoints published by the European Committee on Antimicrobial Susceptibility Testing. Incidence rates were calculated and proportions were compared using the χ 2 test or Fisher’s exact test, and analysed using the Statistical Package for Social Sciences (SPSS 18.0). A total of 14,251 confirmed cases of N. gonorrhoeae were notified. Incidence increased from 30.7 cases/100,000 person-years ( p < 0.001) in 2016 to 64.7 in 2019. Culture was available in 6,292 isolates (44.2%), of which 5,377 (85.5%) were resistant to at least one of the antibiotics tested. Azithromycin resistance rose from 6.1% in 2016 to 16% in 2019 ( p < 0.001). Only 1.0% (45 cases) were resistant to ceftriaxone. Multidrug-resistant N. gonorrhoeae increased from 0.25% in 2016 to 0.42% in 2019 ( p = 0.521). One case presented extensively drug-resistant N. gonorrhoeae . In Catalonia, 10% of the N. gonorrhoeae isolates were resistant to azithromycin in the 2016–2019 period. According to World Health Organization guidelines, resistance above 5% indicates an alert to review treatment guidelines. Antimicrobial susceptibility testing in clinical practice followed by surveillance and interventions are essential to monitor trends and prevent the spread of antimicrobial resistance.

Agroecology as a transformative approach to tackle climatic, food, and ecosystemic crises - Rachel Bezner Kerr; Julio C Postigo; Pete Smith; Annette Cowie; Pramod K Singh; Marta Rivera-Ferre; Maria Cristina Tirado-von der Pahlen; Donovan Campbell; Henry Neufeldt (Current Opinion in Environmental Sustainability, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Seeds of Coronilla talaverae (Fabaceae), an endemic endangered species, in Argaric Early Bronze Age levels of Punta de Gavilanes (Mazarrón, Spain) - Diego Rivera; Milagros Ros-Sala; Concepción Obón; Pedro Sánchez-Gómez; Francisco Alcaraz; Pablo Ferrer; Emilio Laguna; Agustín Lahora; Javier Valera; Maria-Teresa Coronado-Parra; Maria Luisa Precioso (PalZ, 2023)
Punta de Gavilanes (Mazarrón Bay, Spain) was occupied from third millennium cal BC to the first century BC. Overall, the archaeobotanical remains suggest that agriculture and gathering coexisted in the site since the beginning of the occupation of the site. Depending on the sea level variation, the site passed from island in the middle Holocene to peninsula in the late Holocene. Seeds from this archaeological site associated with radiocarbon dates of ≈ 4200 and ≈ 1500 cal years BP include specimens of eight species of shrubs and trees, of which a winter flowering shrub ( Coronilla talaverae Lahora and Sánchez-Gómez), is an endangered species that no longer occurs on Punta de Gavilanes area. The seeds of this endemic Coronilla species are associated with materials dated ≈ 3900 cal years BP in a Bronze Age cultural context. The vanished species was presumably locally exterminated by human alteration of its natural habitat or because of environmental changes. The species of Coronilla identified from Punta de Gavilanes is known from relatively distant seashore areas. This endangered species could be effectively preserved by reintroduction to areas that it occupied prior to human alteration, in particular Punta de los Gavilanes.

The role of spray-drying atmosphere on fridericia chica (bonpl.) L.G. Lohmann standardized extract production for wound healing activity - Ilza Maria de Oliveira Sousa; Gerardo Alvarez Rivera; Diana Pinto; Nubia de Cássia Almeida Queiroz; Veronica Isabel Correia Bastos; Lucia Elaine O. Braga; Josman Dantas Palmeira; Helena Amaral; Helena Maria Neto Ferreira; Helena Cristina Correia Oliveira; Fernando J. Mendes Gonçalves; Ana Lucia T.G Ruiz; et al. (Natural Product Research, 2022)

Experimental investigation to characterize simple versus multi scaling analysis of hydraulic conductivity at a mesoscale - Guglielmo Federico Antonio Brunetti; Samuele De Bartolo; Carmine Fallico; Ferdinando Frega; Maria Fernanda Rivera Velásquez; Gerardo Severino (Stochastic Environmental Research and Risk Assessment, 2022)
The spatial variability of the aquifers' hydraulic properties can be satisfactorily described by means of scaling laws. The latter enable one to relate the small (typically laboratory) scale to the larger (typically formation/regional) ones, therefore leading de facto to an upscaling procedure. In the present study, we are concerned with the spatial variability of the hydraulic conductivity K into a strongly heterogeneous porous formation. A strategy, allowing one to identify correctly the single/multiple scaling of K , is applied for the first time to a large caisson, where the medium was packed. In particular, we show how to identify the various scaling ranges with special emphasis on the determination of the related cut-off limits. Finally, we illustrate how the heterogeneity enhances with the increasing scale of observation, by identifying the proper law accounting for the transition from the laboratory to the field scale. Results of the present study are of paramount utility for the proper design of pumping tests in formations where the degree of spatial variability of the hydraulic conductivity does not allow regarding them as “weakly heterogeneous”, as well as for the study of dispersion mechanisms.

Local canopy disturbance as an explanation for long‐term increases in liana abundance - Stefan A. Schnitzer; David M. DeFilippis; Marco Visser; Sergio Estrada‐Villegas; Rigoberto Rivera‐Camaña; Boris Bernal; Salomé Peréz; Abelino Valdéz; Seberino Valdéz; Antonio Aguilar; James W. Dalling; Eben N. Broadbent; et al. (Ecology Letters, 2021)
Canopy disturbance explains liana abundance and distribution within tropical forests and thus may also explain the widespread pattern of increasing liana abundance; however, this hypothesis remains untested. We used a 10‐year study (2007–2017) of 117,100 rooted lianas in an old‐growth Panamanian forest to test whether local canopy disturbance explains increasing liana abundance. We found that liana density increased 29.2% and basal area 12.5%. The vast majority of these increases were associated with clonal stem proliferation following canopy disturbance, particularly in liana‐dense, low‐canopy gaps, which had far greater liana increases than did undisturbed forest. Lianas may be ecological niche constructors, arresting tree regeneration in gaps and thus creating a high‐light environment that favours sustained liana proliferation. Our findings demonstrate that liana abundance is increasing rapidly and their ability to proliferate via copious clonal stem production in canopy gaps explains much of their increase in this and possibly other tropical forests.

Keeping the ageing brain wired: a role for purine signalling in regulating cellular metabolism in oligodendrocyte progenitors - Andrea D. Rivera; Irene Chacon-De-La-Rocha; Francesca Pieropan; Maria Papanikolau; Kasum Azim; Arthur M. Butt (Pflügers Archiv - European Journal of Physiology, 2021)
White matter (WM) is a highly prominent feature in the human cerebrum and is comprised of bundles of myelinated axons that form the connectome of the brain. Myelin is formed by oligodendrocytes and is essential for rapid neuronal electrical communication that underlies the massive computing power of the human brain. Oligodendrocytes are generated throughout life by oligodendrocyte precursor cells (OPCs), which are identified by expression of the chondroitin sulphate proteoglycan NG2 ( Cspg4 ), and are often termed NG2-glia. Adult NG2+ OPCs are slowly proliferating cells that have the stem cell–like property of self-renewal and differentiation into a pool of ‘late OPCs’ or ‘differentiation committed’ OPCs(COPs) identified by specific expression of the G-protein-coupled receptor GPR17, which are capable of differentiation into myelinating oligodendrocytes. In the adult brain, these reservoirs of OPCs and COPs ensure rapid myelination of new neuronal connections formed in response to neuronal signalling, which underpins learning and cognitive function. However, there is an age-related decline in myelination that is associated with a loss of neuronal function and cognitive decline. The underlying causes of myelin loss in ageing are manifold, but a key factor is the decay in OPC ‘stemness’ and a decline in their replenishment of COPs, which results in the ultimate failure of myelin regeneration. These changes in ageing OPCs are underpinned by dysregulation of neuronal signalling and OPC metabolic function. Here, we highlight the role of purine signalling in regulating OPC self-renewal and the potential importance of GPR17 and the P2X7 receptor subtype in age-related changes in OPC metabolism. Moreover, age is the main factor in the failure of myelination in chronic multiple sclerosis and myelin loss in Alzheimer’s disease, hence understanding the importance of purine signalling in OPC regeneration and myelination is critical for developing new strategies for promoting repair in age-dependent neuropathology.

Evaluation of Cerebellar Function and Integrity of Adult Rats After Long-Term Exposure to Aluminum at Equivalent Urban Region Consumption Concentrations - Rafael Monteiro Fernandes; Priscila Cunha Nascimento; Maria Karolina Martins; Walessa Alana Bragança Aragão; Luis Felipe Sarmiento Rivera; Leonardo Oliveira Bittencourt; Sabrina C. Cartágenes; Maria Elena Crespo-Lopez; Cristiane do Socorro Ferraz Maia; Rafael Rodrigues Lima (Biological Trace Element Research, 2021)

Biofortification of Forage Peas with Combined Application of Selenium and Zinc Under Mediterranean Conditions - Maria D. Reynolds-Marzal; Angélica M. Rivera-Martín; Sara M. Rodrigo; Oscar Santamaria; Maria J. Poblaciones (Journal of Soil Science and Plant Nutrition, 2021)

Characterization of Enterobacter cloacae BAGM01 Producing a Thermostable and Alkaline-Tolerant Rhamnolipid Biosurfactant from the Gulf of Mexico - Nidya Fabiola Curiel-Maciel; Fernando Martínez-Morales; Alexei Fedorovish Licea-Navarro; Brandt Bertrand; A. Berenice Aguilar-Guadarrama; Nashbly Sarela Rosas-Galván; Daniel Morales-Guzmán; Nancy Rivera-Gómez; Rosa Maria Gutiérrez-Ríos; María R. Trejo-Hernández (Marine Biotechnology, 2021)

Traditional ecological knowledge in a ferruginous ecosystem management: lessons for diversifying land use - Lina Marcela Urriago-Ospina; Clarice Morais Jardim; Germán Rivera-Fernández; Alessandra Rodrigues Kozovits; Mariangela Garcia Praça Leite; Maria Cristina Teixeira Braga Messias (Environment, Development and Sustainability, 2021)

Case–Case Comparison of Candida auris Versus Other Candida Species Bloodstream Infections: Results of an Outbreak Investigation in Colombia - Diego H. Caceres; Sandra M. Rivera; Paige A. Armstrong; Patricia Escandon; Nancy A. Chow; Maria Victoria Ovalle; Jorge Díaz; Gordana Derado; Soraya Salcedo; Indira Berrio; Andres Espinosa-Bode; Carmen Varón; et al. (Mycopathologia, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Analysis of inflammatory cytokine expression in the urinary tract of BALB/c mice infected with Proteus (P.) mirabilis and enteroaggregative Escherichia (E.) coli (EAEC) strains - Araceli Melendez-Avalos; Teresita Sainz-Espuñes; Laura Estela Castrillón-Rivera; Felipe Mendoza-Pérez; Alejandro Palma-Ramos; Jorge Ismael Castañeda-Sánchez; Elisa Maria Drago-Serrano (Folia Microbiologica, 2020)

Stable isotope analysis of white-tailed deer teeth as a paleoenvironmental proxy at the Maya site of La Joyanca, northwestern Petén, Guatemala - Maria Rivera-Araya; Kitty F. Emery; M. Charlotte Arnauld; Suzanne Pilaar Birch (Isotopes in Environmental and Health Studies, 2019)

Hatching plasticity and the adaptive benefits of extended embryonic development in glassfrogs - Jesse Delia; Juana Maria Rivera-Ordonez; María José Salazar-Nicholls; Karen M. Warkentin (Evolutionary Ecology, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Andesiops peruvianus (Ephemeroptera: Baetidae): a species complex based on molecular markers and morphology - Paula A. Ossa-López; Maria I. Camargo-Mathias; Fredy A. Rivera-Páez (Hydrobiologia, 2018)

Facilitators of Survivorship Care Among Underserved Breast Cancer Survivors: a Qualitative Study - Amy E. Ustjanauskas; Gwendolyn P. Quinn; Tonya M. Pan; Maria Rivera; Coralia Vázquez-Otero; Danielle Ung; Richard G. Roetzheim; Christine Laronga; Kenneth Johnson; Marilyn Norton; Claudia Carrizosa; Dariana Muñoz; et al. (Journal of Cancer Education, 2017)

TvZNF1 is a C2H2 zinc finger protein of Trichomonas vaginalis - José Luis Villalpando; Rodrigo Arreola; Jonathan Puente-Rivera; Elisa Azuara-Liceaga; Jesús Valdés; Lilia López-Canovas; Alma Villalobos-Osnaya; Maria Elizbeth Alvarez-Sánchez (BioMetals, 2017)

R/Avr gene expression study of Rpi-vnt1.1 transgenic potato resistant to the Phytophthora infestans clonal lineage EC-1 - Maria Lupe Roman; Myriam Izarra; Hannele Lindqvist-Kreuze; Cristina Rivera; Soledad Gamboa; Jose Carlos Tovar; Gregory A. Forbes; Jan F. Kreuze; Marc Ghislain (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Evolutionary Analysis of Pectin Lyases of the Genus Colletotrichum - Alicia Lara-Márquez; Ken Oyama; María G. Zavala-Páramo; Maria G. Villa-Rivera; Ulises Conejo-Saucedo; Horacio Cano-Camacho (Journal of Molecular Evolution, 2017)

Protein homology modeling, docking, and phylogenetic analyses of an endo-1,4-β-xylanase GH11 of Colletotrichum lindemuthianum - Ulises Conejo-Saucedo; Horacio Cano-Camacho; Maria G. Villa-Rivera; Alicia Lara-Márquez; Everardo López-Romero; María G. Zavala-Páramo (Mycological Progress, 2017)

Rpi-blb2 gene from Solanum bulbocastanum confers extreme resistance to late blight disease in potato - Jeanette Orbegozo; Maria Lupe Roman; Cristina Rivera; Soledad Gamboa; Jose Carlos Tovar; Gregory A. Forbes; Hannele Lindqvist-Kreuze; Jan F. Kreuze; Marc Ghislain (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Water Variability and the Economic Impacts on Small-Scale Farmers. A Farm Risk-Based Integrated Modelling Approach - Francisco J. Fernández; Roberto D. Ponce; Maria Blanco; Diego Rivera; Felipe Vásquez (Water Resources Management, 2016)

Two further triple-X/rea(X) females in an inv(X)(p22q22) family - HORACIO RIVERA; ANA I. VÁSQUEZ-VELÁSQUEZ; MARIA G. DOMÍNGUEZ-QUEZADA; AZUBEL RAMÍREZ-VELAZCO (Journal of Genetics, 2016)

Clinical characterization and mutation spectrum in Caribbean Hispanic families with Lynch syndrome - Marcia Cruz-Correa; Yaritza Diaz-Algorri; Julyann Pérez-Mayoral; Wasilah Suleiman-Suleiman; Maria del Mar Gonzalez-Pons; Carlos Bertrán; Nicolás Casellas; Natalia Rodríguez; Sherly Pardo; Keyla Rivera; Rafael Mosquera; Segundo Rodriguez-Quilichini (Familial Cancer, 2015)

Anti-GAD Antibody, Seizures, Cerebellar Ataxias and Vitiligo: A Diagnostic Challenge - Hazael Flores-Cantu; Carlos R. Camara-Lemarroy; Hector J. Calderon-Hernandez; Maria A. Zapata-Rivera; Jesus Z. Villareal-Perez; Hector J. Villareal-Velazquez (The Cerebellum, 2015)

Neuropsychological, Cognitive, and Theoretical Considerations for Evaluation of Bilingual Individuals - Monica Rivera Mindt; Alyssa Arentoft; Kaori Kubo Germano; Erica D’Aquila; Diane Scheiner; Maria Pizzirusso; Tiffany C. Sandoval; Tamar H. Gollan (Neuropsychology Review, 2008)

DNA damage in mouse lymphocytes exposed to curcumin and copper - Patricia Urbina-Cano; Lucina Bobadilla-Morales; Mario A. Ramírez-Herrera; Jorge R. Corona-Rivera; Maria L. Mendoza-Magaña; Rogelio Troyo-Sanromán; Alfredo Corona-Rivera (Journal of Applied Genetics, 2006)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)